The construction of large-aperture Schottky heterostructures and the study of the reduction properties of heavy metal ions under natural light - FengQi Qiu; Yanfei Pan; Yuan Tian; Huiming Shi; Shuaiqi Hu; Qiang Guo; Yuan Wang; Qinglun Liang; Mayin Dai; Zhenhua Xue (Materials & Design)
With the rapid development of industrialization and the reckless discharge of industrial wastewater exacerbating the environmental pollution of water bodies caused by excessive heavy metal ions, the design and preparation of green photocatalysts for the efficient removal of heavy metal ions has attracted much attention. In this study, the one-step construction of lignocellulose-based magnetic photocatalytic composites (NOT-1-1) using lignocellulose as a substrate by a combination of electroless nickel, sol–gel method and high-temperature. The results showed that the hollow pore size of NOT-1-1 was up to 30 μm, and the elements including Ni and Ti were uniformly distributed, which formed TiO2 and Ni-NiO with Schottky heterojunction structure. The composite layer with Schottky heterojunction structure, which improved the photogenerated electron-hole separation ability, and the forbidden band width was only 1.95 eV. The efficient and rapid reduction of Cu(II) under natural light can be realized, and the reduction rate can reach 76.7 % in 15 min, while it was up to 86.7 % after 60 min, and the reduction amount can reach 433.5 mg/g, indicating that excellent photocatalytic reduction performance can be obtained. This study is of great significance for the removal of heavy metal ions from industrial wastewater.